WASTE MANAGEMENT SYSTEM EFFECTIVENESS IN JARING HALUS VILLAGE, SECANGGANG DISTRICT, LANGKAT REGENCY - Ramadhani, Tisya; Aisyah, Dara (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This study seeks to determine and characterize the efficacy of the waste management system in Jaring Halus Village, Secanggang District, Langkat Province. The method of research employed is qualitative research. Interviews, observation, and documentation were employed as data collection technique. The data were then examined using Duncan's theory, which includes the elements of goal attainment, integration, and adaptation. The North Sumatra Provincial Environment Service, the Langkat Regency Environmental Service, the village head and Jaring Halus Village Apparatus, and the Jaring Halus Village Community were among the 11 informants in this study who had knowledge of the waste management system. Based on the findings, it is clear that the waste management system in Jaring Halus Village, Secanggang District, Langkat Province has not been effective. Due to various difficulties, including the absence of solid waste services and monitoring, unsustainable Jumat Bersih and collaboration actions, and the community's continued practice of dumping trash into the sea. One positive outcome of integration has been increased sociability and cooperation among the multiple stakeholders. The waste management system adaptation dimension in the province of North Sumatra has not been as effective as in Langkat Regency, particularly Jaring Halus Village. Due to a lack of resources to support the deployment of the waste management system, the infrastructure is inadequate. Moreover, the capacity of human resources to teach the public remains insufficient.